The Effect of Socio-Economic Conditions on the Happiness Index: ASEAN-8 Study 2015-2021 - Metasari, Amelia; Utomo, Yuni Prihadi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
People’s well-being is a core goal of national development and can be assessed through the happiness index, which reflects overall quality of life. In the face of increasingly complex development challenges across ASEAN, identifying the determinants of happiness is crucial for shaping effective, targeted policies. This study analyzes the impact of various socio-economic and environmental factors—namely Gross Domestic Product (GDP) per capita, labor force, government budgets for education and health, Consumer Price Index (CPI), Corruption Perception Index (CPI), and greenhouse gas emissions per capita—on the happiness index of eight ASEAN countries during 2015–2021. Using panel data analysis, the Fixed Effect Model (FEM) was identified as the best-fit model. The findings reveal that GDP per capita and Corruption Perception Index have a significant negative effect on the happiness index, while education spending and CPI exert a positive influence. Meanwhile, labor force, health budget, and greenhouse gas emissions show no significant impact. Among the observed countries, Singapore ranks highest in happiness, while Cambodia ranks lowest. These results suggest that beyond traditional economic indicators, governance quality—reflected in effective budget allocation and efforts to manage inflation and corruption—plays a vital role in fostering happiness in the ASEAN region.